Quantification of Size Segregated Particulate Matter Deposition in Human Airways - Srimuruganandam, Dr. B; N, Manojkumar; N, Manojkumar; Nagendra, SM Shiva (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 5 No 4 (2018): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Background: Air pollution has become a significant concern in both urban and rural sectors due to its catastrophic effect on human health and the environment. Particulate matter (PM) is crucial among criteria pollutants and is well correlated with human mortality and morbidity. Based on aerodynamic size, PM is classified into coarse (PM10) and fine (PM2.5 and PM1). A recent study by World Health Organization showed that PM has caused 7 million premature deaths globally. Also, the International Agency for Research on Cancer (IARC) identified PM as carcinogenic as it is directly related to lung cancer. Human airway is the primary pathway for PM to enter the human body. Hence the study on coarse and fine PM deposition in the human respiratory tract is essential for health risk assessments. Materials and Methods: Hourly measurements of PM10, PM2.5 and PM1 are measured during a winter using Grimm aerosol spectrometer near an arterial roadside in Chennai city of Tamil Nadu, India. PM deposition in the human airway is investigated using the Multiple-Path Particle Deposition Model (MPPD) version 3.04. In MPPD model, the stochastic structure which depicts the real human lung is considered. The deposition in MPPD model is assessed for three size fractions, i.e. PM10, PM2.5 and PM1 under different breathing scenarios viz. nasal, oral, and oronasal. Results: Highest total deposited mass rate obtained from the MPPD model for PM10, PM2.5, and PM1 are 942 ng min-1, 345 ng min-1, and 104 ng min-1, respectively. The maximum deposited mass rate is also assessed in the head (PM10 = 904 ng min-1; PM2.5 = 244 ng min-1; PM1 = 57 ng min-1), tracheobronchial (PM10 = 284 ng min-1; PM2.5 = 60 ng min-1; PM1 = 24 ng min-1) and pulmonary (PM10 = 32 ng min-1; PM2.5 = 89 ng min-1; PM1 = 27 ng min-1) regions. In the head region, maximum deposition is caused by nasal breathing; whereas, tracheobronchial (TB) and pulmonary regions, the oral breathing leads to higher deposition. Results also showed that for all PM sizes the lobe wise depositions are in the following order: right upper > left lower > left upper > right middle > right lower. Further, the airway clearance results indicated that PM removal is faster in the TB region than the alveolar region. Conclusion: PM10 has a higher deposition in the head region whereas PM2.5 and PM1 deposition is higher in the TB and pulmonary regions. This indicates that PM deposition inside lungs is influenced by its size and several other deposition mechanisms viz. inertial impaction, sedimentation, diffusion and interception. Further, this study results can be utilized for assessing health risks such as oxidative potential and toxicity of deposited PM. How to cite this article: Manojkumar N, Srimuruganandam B, Nagendra SMS. Quantification of Size Segregated Particulate Matter Deposition in Human Airways. J Adv Res Alt Energ Env Eco 2018; 5(4): 15-22. DOI: https://doi.org/10.24321/2455.3093.201803